2021
DOI: 10.3164/jcbn.20-41
|View full text |Cite
|
Sign up to set email alerts
|

The simplified Kyoto classification score is consistent with the ABC method of classification as a grading system for endoscopic gastritis

Abstract: The ABC method combined with Helicobacter pylori antibody and serum pepsinogen is a useful predictive method for stomach cancer. Kyoto classification is a new grading system for endoscopic gastritis. However, the consistency of the Kyoto score with the ABC method remains unclear. The Kyoto classification score, which ranges from 0 to 8, is based on the following findings: atrophy, intestinal metaplasia, diffuse redness, nodularity, and enlarged folds. Furthermore, we defined a simplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Dr. Haruma [24]suggested that serum PG I levels in AIG usually decrease to <25 ng/mL, and AIG is most likely to be diagnosed when its level is <10 ng/mL. Serum PG is also measured during the ABC method, a gastric risk stratification program based on the H. pylori antibody [25-27]. The ABC method focuses on grouping into 4 classifications, causing the PG I value to be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Haruma [24]suggested that serum PG I levels in AIG usually decrease to <25 ng/mL, and AIG is most likely to be diagnosed when its level is <10 ng/mL. Serum PG is also measured during the ABC method, a gastric risk stratification program based on the H. pylori antibody [25-27]. The ABC method focuses on grouping into 4 classifications, causing the PG I value to be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…( 24 , 25 ) The PSCA SNP was also shown to be associated with pathological and serological (i.e., pepsinogen I/II ratio) atrophic gastritis, which partially supports our findings. ( 22 , 31 33 )…”
Section: Discussionmentioning
confidence: 99%
“…The Kyoto classification of gastritis, which is scored from 0 to 8, is based on the sum of scores of the following five endoscopic findings: atrophy, intestinal metaplasia (IM), enlarged folds, nodularity, and diffuse redness. ( 22 ) A high score represents increased risk for gastric cancer and H. pylori infection. ( 14 18 ) Gastric atrophy was classified according to the extent of mucosal atrophy, as described by Kimura and Takemoto.…”
Section: Methodsmentioning
confidence: 99%
“…The Kyoto score for endoscopic gastritis, which ranges from 0 to 8, is based on the total scores of the following five endoscopic findings: atrophy, intestinal metaplasia, enlarged folds, nodularity, and diffuse redness. A high score represents an increased risk of gastric cancer[ 20 - 23 ] and H. pylori infection[ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Kyoto classification adopted and scored atrophy, intestinal metaplasia, enlarged folds, nodularity, diffuse redness, and the regular arrangement of collecting venules (RAC) as endoscopic findings of gastritis. Among them, the Kyoto score, which is the sum of the scores of these factors, has been vigorously reported to be associated with gastric cancer[ 21 , 22 ], gastric cancer risk[ 20 , 23 ], and H. pylori infections[ 24 ]. Evaluating the risk of gastric cancer on the basis of endoscopic findings is an important alternative to biopsy.…”
Section: Introductionmentioning
confidence: 99%